Circadian clock genes in the circadian clock and photoperiodic timer in Pyrrhocoris apterus - Chodáková, Lenka (Jihočeská univerzita, 2019)
This thesis focuses on the circadian clock genes and their involvement in the photoperiodic time measurement in the linden bug, Pyrrhocoris apterus. Application of the molecular biology methods enabled us to propose the architecture of circadian clockwork. We also investigated the role of several previously undescribed players in the circadian clock. Furthermore, by using molecular biology methods we focused on the involvement of core circadian clock genes in the photoperiodism.
Circadian clock genes in the circadian clock and photoperiodic timer in Pyrrhocoris apterus
Keywords: circadian clock; circadian clock genes; photoperiodic timer; Pyrrhocoris apterus; RNAi